THE ROLE HEALTH OFFICERS AS A DETERMINING FACTOR FOR THE SUCCESSFUL MEASLES RUBELLA IMMUNIZATION IN THE WORK AREA OF THE RAWANG HEALTH CENTER, PADANG CITY - Rahmadani, Putri; Besral, Besral; Masrizal, Masrizal (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: The measles rubella (MR) immunization coverage rate in Padang City is only 30.82%, still far below Indonesia's national target of 95%. The coverage of measles rubella immunization at the Rawang Health Center is around 62.1%. This study aims to determine the role of health workers in the success of measles rubella immunization in the Rawang Public Health Center, Padang City. Methods: This study used a cross sectional design. The study was conducted in October 2018-July 2019. The research population is mothers who have children aged 12-59 months (toddlers) as many as 1807 respondents. The sampling method is proportional random sampling with a sample of 87 respondent. Data was collected by interview using a questionnaire. Results: The results showed that 37.9% of children under five had not been immunized against measles rubella and 44.8% of health workers had an unfavorable role. The results of the chi-square test showed a significant relationship  between  the role of officers in  the success of measles rubella immunization  (p-value=0.020). Recommendation: It is hoped that health workers can increase health promotion activities regarding the risks due to children not being immunized against measles rubella and intensify door-to-door programs in the implementation of measles rubella immunization